Bridging Language and Knowledge: Exploring Interdisciplinary Themes in English Textbooks - Poudel, Guru Prasad (Interdisciplinary Research in Education, 2025)
Interdisciplinarity has been a norm in academic reading texts for the purpose of providing exposure to the students in both knowledge and skills across diverse content areas. We find the integration of interdisciplinary texts in our textbooks from primary to tertiary levels. Textbooks play significant role to provide knowledge base by incorporating reading themes from various fields. These texts seem useful to enhance students’ content knowledge together with language competencies. Though increasing integration of interdisciplinary is seen in reading themes, only a few studies have examined how well interdisciplinarity is maintained in reading resources, including textbooks for different grades. Specifically, questions remain as to whether the reading themes and related texts are appropriately aligned and whether the textbooks reflect systematic interdisciplinary integration. Aiming at bridging this gap, this article uncovers reading themes and unveils the extent to which interdisciplinary themes are included into the Grade Nine Compulsory English textbook (2076) in Nepal. Following a qualitative research design, the study uses document analysis method. The findings show that the textbook for grade nine students is a good blend of diverse reading themes, including the texts related to culture, health, science and technology, ethics, sports, ecology and entertainment. A purposeful attempt at interdisciplinary integration has been seen in the texts along with the integration of genres such as informational articles, narratives, memoirs, and poems. Despite the interdisciplinarity, inconsistencies have been observed in theme-text relationship. The over-reliance on certain genres, and absence of scaffolding activities for complex texts are noted as the limitations. The study concludes that though the selected textbook reflects a good interdisciplinarity in its contents, improvements are sought in the text choice, texts organizations, text coherence and in practice activities.